Off-farm income and food expenditure of rural households in China. Issue 5 (25th April 2019) - Liu, Yuying; Renwick, Alan; Fu, Xinhong
Abstract : Purpose: The purpose of this paper is to examine the impact of off-farm income on food expenditure, using survey data of 493 rural households from Gansu, Henan and Shandong provinces in China. Design/methodology/approach: A two-stage least squares estimator is used to jointly estimate the determinants of off-farm income and the direct impact of off-farm income on food expenditure while controlling for the endogeneity issue associated with off-farm income variable. Findings: The empirical results show that gender, education of household head, household size, farm size, the presence of children, smartphone use and asset ownership mainly determine off-farm income, and the off-farm income affects food expenditure of rural households significantly. In particular, the results show that a 1, 000 yuan increase in per capita off-farm income increases per capita food expenditure by 61 yuan. Further estimations reveal that off-farm income has a larger effect on food expenditure of high-income rural households relative to their low-income counterparts. Originality/value: Although poverty implications of off-farm income have been well documented, few studies have analysed the effects of off-farm income on food expenditure of rural households. To the best of the authors' knowledge, there are no studies on this issue that focus on rural China. Therefore, the present study attempts to provide a first insight into the association between off-farm income and food expenditure of rural households in China, with the aim of providing useful evidence for policymakers in their efforts to reduce rural and urban food consumption gap and further increase social welfare.